STRATEGI ADAPTASI USAHA LEMPUK DURIAN DI DESA SELATBARU KECEMATAN BANTAN KABUPATEN BENGKALIS - Handayani, Wahyu; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted in Desa Selatbaru Kecamatan Bantan Kabupaten Bengkalis. The purpose of this study was to determine the fabric artisans strategy lempuk durian maintain culture weaving in Desa Selatbaru Kecamatan Bantan Kabupaten Bengkalis. This study entitled